Monitoring of the Immune Response Activity in Iraqi Patients Infected with Cutaneous Leishmaniasis by IFN-Î³ and MIG Evaluation During Different Stages of Infection - Jameel, Reem Aladdin; Al-Qadhi, B. N. (Iraqi Journal of Science, 2020)
Cutaneous leishmaniasis (CL) is one of the most prevalent cutaneous parasitic protozoan infections in Iraq; characterized by a chronic infection and granulomatous disease that invades the skin. Type 1 immune was predominates in CL patients with exacerbated production of pro-inflammatory cytokine, therefore this study aimed to evaluate serum level of interferon gamma (IFN-Î³) and monokine induce by interferon gamma (MIG/CXCl9) as a useful markers of disease development in patients during different stage of infection (<1 month .. early , 1-6 month.. chronic and >6 months.. late). The result showed that there was an early effort to eliminate the parasite proliferation which illustrated by a high significant increase of both IFN-Î³ and MIG during the early stage of infection, but this response was down-regulated during the chronic stage of infection, which observed by low levels of both studied cytokine and monokine, nevertheless this down-regulation was transient where the levels to increase returns during the late stage of infection. The evaluation of IFN-Î³ and MIG considered as a biological markers of disease activity in each stage of infection.